Penggunaan Setsuzokushi Uchi Ni, Aida Ni, Kagiri Dan Ijou Wa Dalam Novel Tobu Ga Gotoku Karya Ryoutarou Shiba - Prismayanti, Ni Wayan; Yuliani Giri, Ni Luh Kade; Gorethy Nie Nie, Maria (Humanis; Volume 16. No. 3. September 2016, 2016)
This research entitled “The Usage of Setsuzokushi Uchi ni, Aida ni, Kagiri and Ijou wa in Tobu ga Gotoku Novel by Ryoutarou Shiba”. This research describes the structure and contextual meaning of setsuzokushi uchi ni, aida ni, kagiri and ijou wa in Tobu ga Gotoku Novel by Ryoutarou Shiba. The obtained data were analyzed using descriptive analysis method. The theories used for analyzing are syntax theory by Verhaar (2012) and contextual meaning theory by Pateda (2001). As the result, setsuzokushi uchi ni, aida ni, kagiri and ijou wa are always connected with verb, adjective and noun. Setsuzokushi uchi ni and aida ni are not always use their particle “ni” in the sentence. Setsuzokushi ijou wa is not always use it particle “wa” in the sentence. There are four kinds of contextual meaning that found in the setsuzokushi uchi ni’s data, that are situation context, purpose context, mood context and time context. There are three contextual meaning that found in the setsuzokushi aida ni’s data, that are situation context, time context and location context. In the kagiri’s data there are situation context, purpose context and time context. And in the ijou wa’s data there are two context that are person context and purpose context.